Intertemporal approach to the current account: evidence from Malaysia and Indonesia - Ismail, Hamizun; Baharumshah, Ahmad Zubaidi; MacDonald, Ronald (Penerbit Universiti Kebangsaan Malaysia, 2013)
This article presents an application of the intertemporal approach to the current account positions of Indonesia and Malaysia over the past four decades. Comparing the results for these two emerging market economies, the model performed noticeable better for Malaysia. Meanwhile, Indonesia’s external imbalances revealed the followings: deficits of the mid-1980s and 1990s prior to the 1997 crisis appeared to be an unsustainable path; surpluses during the post-crisis period deviated from the ‘optimal path’ significantly, implying that savings had reached a level that was beyond what would be required to support full ‘consumption-smoothing’; and capital movements appeared to be excessively volatile.